Respiratory Syncytial Virus NS1 Protein Targets the Transactivator Binding Domain of MED25. Issue 19 (15th October 2022) - Dong, Jiawei; Basse, Vincent; Bierre, Maxime; Peres de Oliveira, Andressa; Vidalain, Pierre-Olivier; Sibille, Pierre; Tangy, Frederic; Galloux, Marie; Eleouet, Jean-Francois; Sizun, Christina; Bajorek, Monika
Graphical abstract: Highlights: Mediator complex MED25 subunit is identified as an RSV NS1 interactor by Y2H. NS1 directly interacts with MED25 ACID domain via the α, β-core domain and the C-terminal α3. NMR indicates that NS1 α3 primary binds to MED25 H2 face. NS1 can compete with ATF6a transactivation domain binding to MED25. Abstract: Human RSV is the leading cause of infantile bronchiolitis in the world and one of the major causes of childhood deaths in resource-poor settings. It is a major unmet target for vaccines and anti-viral drugs. Respiratory syncytial virus has evolved a unique strategy to evade host immune response by coding for two non-structural proteins NS1 and NS2. Recently it was shown that in infected cells, nuclear NS1 could be involved in transcription regulation of host genes linked to innate immune response, via interactions with chromatin and the Mediator complex. Here we identified the MED25 Mediator subunit as an NS1 interactor in a yeast two-hybrid screen. We demonstrate that NS1 directly interacts with MED25 in vitro and in cellula, and that this interaction involves the MED25 transactivator binding ACID domain on the one hand, and the C-terminal α3 helix of NS1, with an additional contribution of the globular domain of NS1, on the other hand. By NMR we show that the NS1 α3 sequence primarily binds to the MED25 ACID H2 face, similarly to the α-helical transactivation domains (TADs) of transcription regulators such as Herpex simplex VP16 and ATF6α, a master regulator of ER stress response activated upon viral infection. Moreover, we found out that the NS1 could compete with ATF6α TAD for binding to MED25. These findings point to a mechanism of NS1 interfering with innate immune response by impairing recruitment by cellular TADs of the Mediator via MED25 and hence transcription of specific genes by RNA polymerase II.